Peramalan Harga Emas Antam Menggunakan Metode Generalized Autoregressive Conditional Heterokedasticity (GARCH) - Amri, Ihsan Fathoni; Astuti, Sofi Anggi; Sulistiya, Indah; Suherdi, Andri; Haris, M.Al (Mathematics Department, Faculty of Mathematics and Sciences Unisda Lamongan, 2024)
ANTAM gold is a long-term inflation-resistant investment instrument with a low-risk profile. Socio-economic conditions greatly influence gold price fluctuations, so gold price forecasting is very important for investors to understand the dynamic of changes in gold price. This study proposes the Generalized Autoregressive Conditional Heteroscedasticity (GARCH) methods to model the forecasting of gold price fluctuations. The data used is ANTAM’s daily gold price data for the period June 2018 – June 2023. The results show that by using the best ARIMA (0,1,1) GARCH (2,1) model, the gold price forecasting results are in the price range of Rp 947.100.